Uji Aktivitas Ekstrak Etanol Daun Kenikir (Cosmos caudatus Kunth.) Dengan Metode DPPH - Abidin, Zainal; Aminah, Aminah; Sari, Nurmala (PHARMACY UMI JOURNAL SYSTEM, 2024)
Kenikir (Cosmos caudatus Kunth.) is a traditional vegetable that can be eaten raw or cooked as a vegetable. This plant is also used for food flavoring and traditional medicine. In addition, several nutritional and medical studies show that Kenikir is rich in bioactive compounds such as flavonoids, phenols, carbohydrates, minerals, proteins and vitamins, which can increase its nutritional value. This study aims to determine the antioxidant activity of ethanol extract of kenikir leaves (Cosmos caudatus Kunth) using the DPPH method. The results showed that the ethanol extract of kenikir leaves (C. caudatus Kunth) had high antioxidant activity. Antioxidants are substances that can delay, slow down and prevent oxidation. Antioxidants are very beneficial for health and play an important role in maintaining the quality of food products. The antioxidant activity is in the very strong category (<50 ppm), namely 25,212 ppm. The macerated extract showed the highest antioxidant activity because it contained many secondary metabolites such as flavonoids and phenolics.